Patterns of Self-Care Behaviors and Their Influence on Maintaining Independence: The National Health and Aging Trends Study - Mielenz, Thelma J.; Kannoth, Sneha; Xue, Qian-Li (Frontiers in Aging, 2021)
Importance: Few studies have addressed the combined effects of health-promoting and self-care behaviors among older adults. Thus, new research is needed to assess the potential for behavior change to prolong independence in later life. Objectives: To determine the relationships between self-care behaviors and risks of mobility and activities of daily living (ADLs) over time. Design: Longitudinal data was used from the National Health and Aging Trends Study (NHATS) cohort. Eight baseline self-care behaviors were summarized using latent class analysis. Separately, longitudinal latent classes of mobility and ADLs were created. Setting: Annual in-person interviews conducted for a nationally representative sample. Participants: The baseline study sample included 7609 Medicare beneficiaries aged ≥65 from NHATS who were living in community or residential care settings, with a 71% response rate. The average age was 75, with 57% female, 81% white and 78% high school graduates or higher. Approximately, 80% (n=6064) completed five years of follow-up. Exposures: Favorable vs. unfavorable self-care latent classes measured at baseline. Main outcomes and Measures: Associations were measured between baseline classes and longitudinal classes of mobility and ADLs difficulty. Among decedents, five-year associations were measured between baseline classes and years of overall, healthy, able, and healthy/able life. Results: Two habitual baseline self-care behavioral patterns (46% favorable; 54% unfavorable) and three trajectories of change in mobility and ADLs disability (maintaining independence; shifting to accommodation/difficulty; shifting to assistance) emerged over time. Participants with a favorable baseline pattern had 92%(0.90-0.94) reduced risk in shifting to assistance class and 70%(0.64-0.76) reduced risk for shifting to accommodation/difficulty class for mobility disability. Participants with a favorable baseline pattern had 86%(0.83-0.89) reduced risk in shifting to assistance class and 24%(0.11-0.36) reduced risk in shifting to accommodation/difficulty class for ADLs disability. Those with an unfavorable pattern had 2.54 times greater risk of mortality by the end of the 5-year follow-up compared to those with a favorable pattern. Conclusion: Self-care behaviors in older age represent a habitual pattern. A favorable self-care behavioral pattern decreased the risk of moving towards a more disabled profile and added years of life. Interventions should encourage self-care behaviors constituting a favorable pattern.